Burkholderia pseudomallei: an update on disease, virulence and host interaction - Lee, S.H.; Nathan, S. (Penerbit Universiti Kebangsaan Malaysia, 2013)
Burkholderia pseudomallei is the etiological agent of melioidosis, a life-threatening disease of humans and animals that occurs primarily in Southeast Asia and northern Australia. The distribution of B. pseudomallei and occurrence of melioidosis globally is very much evident. This soil and water-dwelling saprophyte is resilient to various environments. This organism has gained further notoriety following the Centre for Disease Control’s classification of B. pseudomalleias a Tier 1 biological agent. Despite several decades of clinical research, the mortality rate for melioidosis remains high. Genomics-based studies have demonstrated the plasticity of the B. pseudomallei genome and the coding sequences consists of a myriad of functions that enable the bacteria to adapt to these hostile environments as well as various hosts. Diagnosis is mainly based on bacterial culture or serological assays whilst treatment is limited to third generation cephalosporins. To date, no vaccine is currently available as an immunoprophylaxis for melioidosis. By utilising the available genome sequence, a number of virulence factors have recently been identified and have provided more insight into the pathogenesis of B. pseudomallei. These factors include surface associated proteins as well as secreted effector proteins and their corresponding secretion systems. In addition, a number of recent studies on host-pathogen interaction have also demonstrated how the pathogen is able to subvert the host immune system and survive within the cell. This review presents an overview of the current understanding on B. pseudomallei pathogenesis and the disease melioidosis.